Relational factors of senior secondary school students' preference for teaching profession (2014)
This study investigated the Relational Factors of Students preference for teaching profession. Six hundred seniorsecondary school II studetns and their parents were selected through multi stage sampling technique. Three instruments were used for data collection: students teaching profession preference scale(r=0.70), salary and incentive scale (r=0.89) and Parental career value scale (r=0.51) validated using Cronbach Alpha reliability analysis. The data collected were analysed using descriptive statistics and multiple regression. Level of significance was taken to be 0.05. Students' preference for teaching profession was found to be positive. It was also discovered that teaching profession is rated 5th out of 10th position to parents. The study also revealed that parental creer value, salary and gender compositely predict students' preference for teaching profession R=.291;F(3.471) = 14.503,p<0.05). Subsequently when the relative contribution of the independent varirables were looked into, only salary was the significant influential varirable (salary β=.287, t=6.498,p<0.05) while parental career value and gender were not. Based on the findings of this study, it was recommended that government motivate teachers with better salary and provide good working enviroment to improve the image of teachers. It was slso recommended that government, policy makers, curriculum planners should set up a scheme to encourage hard working teachers by promoting them annually and sending them on training abroad.